2017
DOI: 10.7554/elife.28197
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological evidence of efference copies to inner speech

Abstract: Efference copies refer to internal duplicates of movement-producing neural signals. Their primary function is to predict, and often suppress, the sensory consequences of willed movements. Efference copies have been almost exclusively investigated in the context of overt movements. The current electrophysiological study employed a novel design to show that inner speech – the silent production of words in one’s mind – is also associated with an efference copy. Participants produced an inner phoneme at a precisel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 81 publications
(125 reference statements)
8
68
0
Order By: Relevance
“…Movement‐specific information, however, is needed to accurately predict sensory consequences of any movement and reduce the prediction error. This also accords with previous observations which showed that the efference copy (motor command copy) conveys the details of auditory properties in inner speech scenario (Whitford et al, ). Similarly, it has been shown that beta oscillations before a movement contain information about future movement (Pape & Siegel, ; Tan et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Movement‐specific information, however, is needed to accurately predict sensory consequences of any movement and reduce the prediction error. This also accords with previous observations which showed that the efference copy (motor command copy) conveys the details of auditory properties in inner speech scenario (Whitford et al, ). Similarly, it has been shown that beta oscillations before a movement contain information about future movement (Pape & Siegel, ; Tan et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Such activations were evident in all self-generated verbal tasks employed in our study as well, such as word fluency and working memory (see figure 4C-E). These results are compatible with recent empiric evidence that inner speech -a purely mental action -is associated with an efference copy, previously associated only to overt movements, thus suggesting that inner speech may reflect a special type of overt speech 44 .…”
Section: Discussionsupporting
confidence: 91%
“…For this reason, we are hesitant to refer to the "weaker" version of the motor theory as a theory of speech perception at all. Instead, it is a MOTOR CONTRIBUTION TO SPEECH PERCEPTION 20 rather simplistic characterization of a class of sensorimotor interactions that: (a) are observable under a limited set of circumstances in the context of speech; (b) are likely not specific to speech (Morillon et al, 2015); and (c) may even be harmful to speech perception in some cases (Hickok, 2014;Whitford et al, 2017). The straightest path toward understanding human speech processing from any perspective -sensory, motor, or sensorimotor -is to put the motor theory of speech perception to bed for good.…”
Section: Motor Contribution To Speech Perception 19mentioning
confidence: 99%